Essential Of Corporate Governance On Performance Of Commercial Banking Institution S In Southeast Asia And East Asia - Tan, Xing Hau (2022)
Corporate governance (CG) is growing and has become an essential mechanism that affects the firm’s performance, especially financial institutions. The widespread corruption cases in ASEAN countries generally reflect the weak governance in SEA and EA countries. In order to deter the widespread corruption that threatens economic growth, strong corporate governance structures of banking institutions have become essential than ever. In fact, a number of previous studies examined the association between CG and banks’ performance. However, there is a lack of research that comparing the roles of CG in SEA and EA countries. This paper aims to more precisely examine the impact of CG mechanisms on the commercial bank’s performance across SEA and EA countries. This paper has involved five corporate governance variables, board size, number of non-executive directors, the existence of female directors, CEO duality, and the existence of CEO on the board while controlling the bank-specific factors such as bank size and bank liquidity. Moreover, the assets on asset and return on equity will be used to measure the performance or value of commercial banks. Besides, this paper tested a total sample of 99 commercial banks across SEA and EA countries for 2020 by carrying out a cross-sectional regression analysis. This study reveals that the board size, existence of non-executive director, and presence of CEO in the boardroom are typically demonstrated mixed relationship, while CEO duality is negative significantly influence on the CB’s performance. Lastly, there is a significant finding in this paper, whereby the presence of the female director in the boardroom display an adverse correlation with the CB’s performance. This finding is contradict with the mandatory pass by many countries to promote the gender diversified boardroom.